WordNet-SALDO - Språkbanken Text (University of Gothenburg, 2024)
A linking between SALDO senses and Core WordNet

En länkning mellan SALDO och Core WordNet
WordNet-SALDO
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik